1994
DOI: 10.1128/aem.60.6.1789-1797.1994
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the taxonomy, serology, drug resistance transfer, and virulence of Citrobacter freundii strains from mammals and poikilothermic hosts

Abstract: In this study, the phenotypic, antigenic, and virulence characteristics of 32 Citrobacterfreundii strains of fish, human, and veterinary origin were comparatively analyzed. In addition, the spread of drug resistance factors by conjugation was investigated. Regardless of the source of isolation, the strains exhibited variable reactions mainly for arginine dihydrolase, ornithine decarboxylase, and fermentation of sucrose, melibiose, amygdalin, and salicin. Total fatty acid methyl ester analysis by gas chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The genus Citrobacter in the Enterobacteriaceae family consists of 13 currently recognized species, and among these, Citrobacter freundii and Citrobacter koseri are the most frequently associated with infection of humans. C. freundii , the focus of this study, can be found in the intestinal tracts of humans and other animals and from diverse environmental sources 8 – 10 . Previous studies have described the isolation of enterotoxin-producing C. freundii in association with diarrhea 11 13 ; however, such toxigenic C. freundii appear to be uncommon and the primary impact of C. freundii on human health is arguably as an opportunistic pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Citrobacter in the Enterobacteriaceae family consists of 13 currently recognized species, and among these, Citrobacter freundii and Citrobacter koseri are the most frequently associated with infection of humans. C. freundii , the focus of this study, can be found in the intestinal tracts of humans and other animals and from diverse environmental sources 8 – 10 . Previous studies have described the isolation of enterotoxin-producing C. freundii in association with diarrhea 11 13 ; however, such toxigenic C. freundii appear to be uncommon and the primary impact of C. freundii on human health is arguably as an opportunistic pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that LD 50 of C. freundii was ( 1×10 7 ) cfu/rat as showen in Table (1 ) and Fig ( 1) and the LD50 of heat killed E.coli was 2.3× 10 8. , While the lethal dose that killed half number of rats that injected with EXP was 390 mg/rat Table (2 ) LD50 = 1600-( 6.050/ 5) = 390 mg/ml The phagocytic activity was increased significantly (P ˂ 0.05 ) in the rats after treatment with EXP , Killed antigen and whole bacteria in compare to control group , Also the results explain that EXPvaccine were significantly elevated the mean of phagocytosis ( 73 and 80 ) respectively in rats treated after first and post dose that revealed highest increase in phagocytosis in compare with rats treated with HK E.coli and whole bacteria the results recorded that mean of phagocytic activity for Killed bacteria was ( 56 and 60 ) respectively after first and post doses in compare with control group ( 30 ) as showen in Fig( 2)…”
Section: -Ld 50 For a Live Suspension Of C Freundiimentioning
confidence: 67%
“…While , (3) founded that 50% lethel dose for C.freundii suspension was 3.16 ×10 6 . C.freundii isolated from different clinical source produce different LD50 value for example LD50 from feces of patient in USA was 1.5×10 7 , while 9×10 7 from skin ulcer in spain patient (30) The results of LD50 for HK E.coli was nearly acoording to (31) who found that LD50 HK E.coli was 0.83×10 8 and (19) they found that HK E.coli was 1×10 8 .…”
Section: Discussionmentioning
confidence: 94%
“…The most rapid mortality rate was apparent among fish infected with 4 × 10 7 CFU/fish. The calculated LD 50 value was 7.3 × 10 6 CFU/fish, which was lower than that of C. freundii [31]. As the LD 50 value exceeded 10 6 CFU/fish, the bacterium cannot be considered a serious fish pathogen.…”
Section: Pathogenicity Of Strain Snu Wt2 and Histopathological Findingsmentioning
confidence: 81%